2019
DOI: 10.3390/ijms20215384
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Effects of Sulforaphane and Capsaicin on Metabolism upon Androgen and Tip60 Activation of Androgen Receptor

Abstract: Androgen receptor (AR) stimulators, such as androgen and Tip60, play a pivotal role in prostatic carcinogenesis as androgen receptor signaling is critical for the growth and transformation of the prostate gland. Moreover, androgen and Tip60 promotes HIF-1α activation, involved in metabolic reprogramming by increasing glycolysis, a hallmark in cancer initiation and development. In this study we evaluated the effect of androgen and Tip60 stimulus in AR pathway activation and HIF-1α stabilization, in terms of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 59 publications
(74 reference statements)
3
29
0
Order By: Relevance
“…Consistent with other cancer types, an increase in glucose uptake or transporter is also associated with elevated glycolytic activity and emerging evidence has established the significance of the AR in glycolysis [7,9,10]. This is demonstrated by the increase in extracellular acidification rate, an indicator of glycolytic activity, following androgen treatment in androgen-dependent LNCaP and VCaP cells [7,[29][30][31]. The VCaP cell line was established from metastatic bone cancer and has amplified expression of the wild-type AR [39,40].…”
Section: Molecular Effects Of the Ar On Glucose Metabolismmentioning
confidence: 82%
See 3 more Smart Citations
“…Consistent with other cancer types, an increase in glucose uptake or transporter is also associated with elevated glycolytic activity and emerging evidence has established the significance of the AR in glycolysis [7,9,10]. This is demonstrated by the increase in extracellular acidification rate, an indicator of glycolytic activity, following androgen treatment in androgen-dependent LNCaP and VCaP cells [7,[29][30][31]. The VCaP cell line was established from metastatic bone cancer and has amplified expression of the wild-type AR [39,40].…”
Section: Molecular Effects Of the Ar On Glucose Metabolismmentioning
confidence: 82%
“…In fact, in human biopsies of hormone refractory prostate cancer, an increase in Tip60 expression and nuclear accumulation was observed compared to benign prostate hyperplasia and primary prostate cancer, in which a more cytoplasmic distribution was detected [89]. Interestingly, although AR activation mediated by Tip60 is associated with the presence of androgen stimulus, AR activation could be induced even in the absence of androgens when Tip60 is highly overexpressed [23,31]. A recent study has further demonstrated that overexpression of Tip60 alone was sufficient to increase cell proliferation and glycolytic activity, most probably through the stabilization of HIF-1α in LNCaP cells [31].…”
Section: Tip60 As Potential Therapeutic Target In Prostate Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…The melanoma cells A375 cells (ATCC ® CRL-1619™) were used in this study for the epidemiological relevance of this type of cancer, as melanoma accounts for the majority of skin cancer deaths and its incidence has risen faster than almost any other cancer [ 49 ]. A375 cells were infected with purified lentiviral particles for red fluorescence protein and expanded as we previously described [ 50 ].…”
Section: Methodsmentioning
confidence: 99%